Pemanfaatan Sosialisasi Digital untuk Meningkatkan Kesadaran Keamanan Jaringan di Masyarakat Desa - Amelia Nur Azizah; Fadila Nur Syifa; Marcha Putri Ramadhanti; Kharisma Yulia Fauzi (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
The rapid use of the internet in public spaces increases the need for free connectivity, such as public Wi-Fi. However, the low digital literacy of the community makes them vulnerable to various cyber attacks such as data theft, malware distribution, and man-in-the-middle attacks. This study aims to analyze the effectiveness of socialization activities as a means of increasing awareness of network security in rural communities. The activities were carried out in Darmakradenan Village, Grumbul Karangpucung using a participatory method based on direct education. The results showed an increase in public understanding of public network threats and preventive measures such as the use of VPNs and network security verification. This study shows that community-based socialization is effective in building a safe and wise digital culture at the local level.